2014
DOI: 10.1134/s0026893314050185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tissue-specific differentially methylated genes with differential gene expression in non-small cell lung cancers

Abstract: Adenocarcinoma (ADC) and squamous cell carcinomas (SCC) are two subtypes of non small cell lung carcinomas which are regarded as the leading cause of cancer related malignancy worldwide. The aim of this study was to detect the differentially methylated loci (DML) and differentially methylated genes (DMGs) of these two tumor sets, and then to illustrate the different expression levels of specific methylated genes. Using the TCGA database and Illumina HumanMethylation27 arrays, we first screened the DMGs and DML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Moreover, those HR values were less than 1, and these two genes were hypermethylated, suggesting genes B3GALT2 and VSIG2 with hypermethylated-down-regulation were protective genes. In a former study, 1 down-regulated gene B3GALT2 was identified among 139 LUAD-specific hypermethylated genes ( Yin et al, 2014 ), which is in line with our results. B3GALT2 is applied to form a prognostic biomarker of carcinoma-associated fibroblasts in NSCLC ( Navab et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, those HR values were less than 1, and these two genes were hypermethylated, suggesting genes B3GALT2 and VSIG2 with hypermethylated-down-regulation were protective genes. In a former study, 1 down-regulated gene B3GALT2 was identified among 139 LUAD-specific hypermethylated genes ( Yin et al, 2014 ), which is in line with our results. B3GALT2 is applied to form a prognostic biomarker of carcinoma-associated fibroblasts in NSCLC ( Navab et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…The reliability of this method was underscored by the substantial literature support for more than 77% of SPDEF’s regulatees, highlighting their close interaction with NSCLC ( Figure 6B ). These regulatees encompass a diverse range of biomolecules, including early-stage biomarkers (ATXN10 55 ), validated therapeutic targets (TCP1 56 ), small-nuclear RNAs with prognostic potentials (SNORA7B 57,58 ), and genes that control migration and invasion of NSCLC (SERINC2 59 and VANGL2 60 ). For instance, the long noncoding RNA (lncRNA) RP11-523H20.3 61 has been demonstrated to be related with the proliferation and metastasis of NSCLC.…”
Section: Resultsmentioning
confidence: 99%